Optimization of Parameters of Asymptotically Stable Systems. (15th February 2011) - Guerman, Anna; Seabra, Ana; Smirnov, Georgi
Abstract : This work deals with numerical methods of parameter optimization for asymptotically stable systems. We formulate a special mathematical programming problem that allows us to determine optimal parameters of a stabilizer. This problem involves solutions to a differential equation. We show how to chose the mesh in order to obtain discrete problem guaranteeing the necessary accuracy. The developed methodology is illustrated by an example concerning optimization of parameters for a satellite stabilization system.